El periódico mural - Perez Rojas, David Joel (2019)
Through the development of this Learning Session it is intended to build in the student the information necessary to understand, process and produce information. The way in which students define and recognize the media and information will be taken into account if they are able to inform themselves by clearly reaching out to others what they wish to express and understand what others intend to communicate. Reading for pleasure will be stimulated, that they define with their own words the concepts raised and recognize their structure of school information media, so that they have prior knowledge for a future elaboration of them.The month of October and all its historical events are reason for the session to develop contextually and adequately.